Espacios para la colectividad en el río de Oro en los municipios de Bucaramanga y Girón – Santander - Betancourt Salamanca, Jorge Armando; Rincón Pico, Oscar Iván (Universidad Antonio Nariño, 2022)
The project Espacios para la colectividad en el río de Oro en los municipios de Bucaramanga y Girón – Santander is developed in the sector between the east side of the industrial park II of the municipality of Bucaramanga and the west side of the municipality of Girón, where it is currently located. is the informal settlement Río de Oro and its zone of influence.